(untitled) (JED (Jurnal Etika Demokrasi), 2022)
The problem in this research is the existence of public opinion about the election results based on the results of surveys and quick counts conducted by survey institutions. It is often the case that the results of survey institutions differ not only in terms of the percentage of numbers, but also in terms of the winnings of different candidates. This raises public unrest. This study aims to determine the role of statistics in general elections through quick counts. The method used in this study uses the library research method. Data collection uses secondary data in the form of research results such as scientific reading books, scientific journals, and research reports. The data analysis technique takes three stages, namely; organize, synthesize and identify controversial issues. The results of this study show that statistics play a role in the quick count as a predictor of election results. Statistics has provided simple techniques in classifying data and in presenting data more easily. This research concludes that Statistical data and methods play a major role, so that their implementation is subject to scientific principles and can be rationally accounted for. Science remains to the fore and objectivity of quick calculations can help the public to obtain comparative information so that all electoral processes and determinations can be monitored.